2011
DOI: 10.1111/j.1365-2230.2011.04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the LPAR6 and LIPH genes underlie autosomal recessive hypotrichosis/woolly hair in 17 consanguineous families from Pakistan

Abstract: Mutations identified in the present study extend the body of evidence implicating LPAR6 and LIPH genes in pathogenesis of human hereditary hair loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 8 publications
3
30
1
Order By: Relevance
“…The 2-bp deletion mutation detected in three families has been previously reported in six other Pakistani families. 1 Interestingly, all nine families carrying the 2-bp deletion mutation originated from (Figs 1,2), it was observed that the deletion mutation appeared on very similar background, suggesting that the mutation in these families was due to the same mutation event. Further, the deletion mutation results in the elimination of the lid peptide sequence which, along with the b9 loop, is required for substrate recognition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 2-bp deletion mutation detected in three families has been previously reported in six other Pakistani families. 1 Interestingly, all nine families carrying the 2-bp deletion mutation originated from (Figs 1,2), it was observed that the deletion mutation appeared on very similar background, suggesting that the mutation in these families was due to the same mutation event. Further, the deletion mutation results in the elimination of the lid peptide sequence which, along with the b9 loop, is required for substrate recognition.…”
Section: Discussionmentioning
confidence: 92%
“…However, a genotype-phenotype correlation has not been defined clearly, as the severity of hair anomalies resulting from the mutations in these two genes is variable, even among affected members in the same family. 1,8 The LIPH and LPAR6 genes are involved in the same signalling pathway of regulating hair growth and differentiation. 4,6 Pasternack and colleagues 6 have shown that oleoyl-Lalpha-lysophosphatidic acid (LPA), produced from phosphatidic acid by LIPH, serves as a ligand for lysophosphatidic acid receptor 6 (P2Y5) encoded by the LPAR6 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the involvement of the receptors LPA 4 , LPA 5 and LPA 6 in cancers. Intriguingly, LPA 6 (P2Y5) is so far the sole LPA receptor whose mutation is responsible for a human disease, as found in cases of Pakistani and Turkish families with autosomal recessive hypotrichosis [16,17], and was also found to be associated with hereditary bladder tumors [18]. The P2Y5 gene (P2RY5) is located within the tumor suppressor retinoblastoma RB1 (intron 17) in a reverse orientation [19].…”
Section: Involvement Of Lpa Receptors In Cancermentioning
confidence: 98%
“…This substitution resulted in replacing the negatively charged aspartic acid residue with a nonpolar aliphatic valine at position 63 (p.D63V) of LPAR6. Sequence analysis of the LPAR6 in the affected members of other three families (B, C, D) revealed the other reported missense mutation involving substitution of Isoleucine with Phenylalanine at amino acid position 188 (c.562A>T, p.I188F) (Figure 2) [3].…”
Section: Resultsmentioning
confidence: 89%
“…Except in two cases [1], [2], the underlying disease causing genes in rest of the six forms of hypotrichosis have been reported. Mutations in two of these genes, LPAR6 and LIPH , result in similar features including hypotrichosis and woolly hair [3]. Presence of woolly hair has also been reported in patients carrying mutations in keratin-74 gene with phenotype segregating in autosomal dominant fashion [4].…”
Section: Introductionmentioning
confidence: 90%